Integrating Customer Relationship Systems: adoption motivations and their impact on CRM feature selection : An exploratory research study in The Netherlands - Gigase, Maarten (My University, 2021)
This Master’s thesis in Information Management aims to support organizations make suitable CRM adoption decisions. The motivation for this research erupted from the fact that organizations looking to adopt new business technologies in the current environment are faced with an overload of alternatives. CRM is the biggest organizational software market. Big data analytics has created endless possibilities for CRM processes but is a double-edged sword. It has simultaneously caused data and CRM feature integrations to become the main obstacles for organizations trying to achieve a successful CRM strategy. A reduction in the adoption of abundant features helps to reduce the size of those issues. This reduction can be enabled by gaining a better understanding of adoption 0motivations since it allows for a more careful pre-adoption selection process. Moreover, knowing the effort it takes to implement the most common CRM features will help organizations in knowing what they are getting into. The five main motivations for overall CRM adoption were identified, just like the nine most common CRM features. This thesis conducted survey research among a sample of CRM experts in The Netherlands to grasp the importance of those five adoption motivations among the variety of CRM features. The CRM features were subsequently ranked in terms of the effort it takes to be implemented into an organization. Findings include that cost reduction remains the dominant adoption motivation, and increasing customer satisfaction has grown in importance over the past decade. More specifically, findings include that features with a strategic functionality – Lead, Contact, and Opportunity Management – are more likely to be adopted when increasing customer satisfaction is the main adoption motivation. Features with an operational functionality – such as Sales and Marketing Automation – are still mainly adopted to reduce costs in operations. Findings for the effort of implementation include that Reports & Dashboard features are most difficult to implement, which is suspected to be due to the need to integrate many tools and data sources for it to be beneficial. Features within the strategic functionality domain are generally easiest to implement. Adoption motivations can be correlated but these correlations are always negative or insignificant. Future research in this domain is suggested to focus on linking organizational competencies to best fitting CRM features and helping organizations in gaining insights on which CRM features are beneficial in separate stages of a business life cycle.
Keywords: CRM, CRM Features, Business Technology, Technology adoption, Adoption motivations, Data integration